ANALISIS PERBANDINGAN GAYA BAHASA PADA LIRIK LAGU THE FIGHTING BOYS DAN COBOY JUNIOR DALAM BAHASA MANDARIN DAN BAHASA INDONESIA - Jan, Jiu; Lily Thamrin; Lusi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study conducts a comparative analysis of the similarities and differences in the use of rhetorical devices in the lyrics of the albums by The Fighting Boys and Coboy Junior. The research employs a qualitative descriptive method combined with a comparative analysis approach. The research objects are four songs from the album Youth Training Manual by The Fighting Boys and four songs from the album Kamu by Coboy Junior. The rhetorical devices used in these lyrics are systematically identified, classified, and compared. The results show that Chinese lyrics tend to employ rhetorical devices such as metaphor, personification, hyperbole, metonymy, parallelism, antithesis, and repetition, emphasizing themes of youth development, dreams, and faith. Meanwhile, Indonesian lyrics commonly use hyperbole, pleonasm, alliteration, assonance, and inversion, highlighting themes of love, friendship, courage, and team spirit. From the perspective of rhetorical devices, Chinese lyrics demonstrate a relatively greater variety of rhetorical forms, resulting in richer expressions. This is related to the more comprehensive and diverse theoretical system of Chinese rhetoric, which is often used to enhance imagery and deepen the ideological meaning of the lyrics. In contrast, Indonesian lyrics use fewer rhetorical devices and tend to express emotions more directly, making the lyrics more rhythmic and engaging. Although the lyrics from both countries focus on themes of youth, dreams, and emotions, differences can be observed in their modes of expression and cultural values. Chinese lyrics tend to emphasize symbolic meaning and spiritual aspirations, whereas Indonesian lyrics highlight direct emotional expression and youthful vitality.